Digital maturity of forecasting and its impact in times of crisis - Julia Eichholz; Thorsten Knauer; Sandra Winkelmann (Schmalenbach Journal of Business Research (SBUR), 2023)
Especially in times of crisis, reliable predictions about probable future developments are difficult, but critical for successfully managing business operations. At the same time, it remains unclear what constitutes a good forecasting process during crises. The aim of this study is to analyze whether and how digital transformation can enhance forecasting processes and enable firms to better deal with crises. To do so, we refer to the concept of digital maturity, i.e., the extent to which digital transformation is adopted in internal processes, studied at the practice of forecasting. Specifically, we analyze whether digitally more mature forecasting processes positively influence (1) satisfaction with forecasting during crises, (2) the effectiveness of countermeasures, and (3) the economic situation during crises. We conduct a cross-sectional survey among 195 medium-sized and large companies in Germany to shed light on the forecasting process and its digital maturity as well as on the impact of the COVID-19 economic crisis on companies. Based on ordinary least squares (OLS) regression, we find that digitally more mature forecasts increase satisfaction with forecasting and the effectiveness of countermeasures. Overall, this study provides new insights into relevant aspects of forecasting to support successful crisis management, and it highlights the importance of advancing digital transformation in forecasting, especially to successfully deal with crises.
Keywords: M10; M41; 650; Crisis management; Digital maturity; Forecasting; Information technology; Management accounting